Microencapsulation of thyme oil by coacervation - Martins, I.M. (2010)
In this work we have developed a process to encapsulate thyme oil using PLA as the wall material. Firstly, an oil-in-water (o/w) emulsion stabilized with tween 20 (HLB of 16,7) and a solution of PLA in dimethylformamide (DMF) have been prepared. Thereafter, the PLA solution was added to the previously prepared o/w emulsion. The o/w emulsion was obtained by dispersion with an ultraturrax and the encapsulation process proceeded under stirring using an impeller stirrer in a batch actor. The microcapsules formed were hardened by adding octamethylcyclotetrasiloxane and allowed to stand during one hour. After this step, they were decanted and washed with pluronicÒ F68 solution (0.1% w/w), an ethanol solution (30% v/v), and hexane. Finally, the microcapsules were freeze-dried during 24h.